2020
DOI: 10.12973/eu-jer.9.2.853
|View full text |Cite
|
Sign up to set email alerts
|

QASEE: A Potential Learning Model to Improve the Critical Thinking Skills of Pre-service Teachers with Different Academic Abilities

Abstract: Research on critical thinking skills has been frequently carried out, but it has not shown maximum results. This problem is exacerbated by the differences in pre-service teachers' academic abilities. A new learning model that can improve pre-service teachers' critical thinking skills and reduce the gap in critical thinking skills among the upper, middle, and lower academic ability pre-service teachers is needed. This research aims at exploring the potential of the QASEE learning model on the critical thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…the evaluating activity that facilitates the development of metacognition (Duman & Semerci, 2019;Zhang & Patrick, 2012), is confirmed to be identical with evaluative questions as stated by Chin & Brown (2002). The research results by Saputri et al (2020) show that the QASEE learning model developed successfully increases the critical thinking skills of different academic ability pre-service teachers. In fact, the corrected mean score of critical thinking skills of the lower academic ability pre-service teachers in the QASEE class is higher than that of the lower academic ability pre-service teachers in the RQA class.…”
Section: Introductionmentioning
confidence: 69%
“…the evaluating activity that facilitates the development of metacognition (Duman & Semerci, 2019;Zhang & Patrick, 2012), is confirmed to be identical with evaluative questions as stated by Chin & Brown (2002). The research results by Saputri et al (2020) show that the QASEE learning model developed successfully increases the critical thinking skills of different academic ability pre-service teachers. In fact, the corrected mean score of critical thinking skills of the lower academic ability pre-service teachers in the QASEE class is higher than that of the lower academic ability pre-service teachers in the RQA class.…”
Section: Introductionmentioning
confidence: 69%
“…In this case, self-reflection is also a part of metacognitive activity, so that this activity can indirectly become an effective means to train pre-service teachers' metacognitive skills (Martin-Gamez et al, 2016;Pantiwati & Husamah, 2017) and academic performance (Yusuff, 2015). Thus, the QASEE learning model is not only effective in facilitating the improvement of critical thinking skills (Saputri et al, 2020), but also in improving metacognitive skills and also cognitive learning outcomes.…”
Section: B) Differences In the Regression Equations Of The Correlation Between Preservice Teachers' Metacognitive Skills And Cognitive Lementioning
confidence: 99%
“…Finally, at the evaluating stage, pre-service teachers are directed to evaluate the whole learning processes. The overall syntax in the QASEE learning model has been reported having potential to improve the critical thinking skills of pre-service teacher with different academic abilities (Saputri et al, 2020). Furthermore, related research conducted by Amin et al, (2020) revealed that there was a correlation between metacognitive skills and critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of metacognitive skills based on planning, self-monitoring, evaluation, and reflection must be supported by preservice teacher courses in universities (Saputri et al, 2020), as these skills allow preservice teachers the flexibility to plan their learning and directly influence learning behaviors, which in turn affects their students' learning outcomes (Veenman, 2008). Preservice teachers who have a strong understanding of how to learn will undoubtedly have confidence in the teaching and learning processes, which will enable them to become lifelong learners who constantly build or enhance their learning quality.…”
Section: Introductionmentioning
confidence: 99%